Reflections on the research of Dr. Tammam Hassan (Damascus University Journal of arts and humanities sciences, 2021)
Voice research among the first Arabs is considered one of the leading and authentic researches in Arab heritage, and its scholars have made outstanding efforts that have been tracked by many modern linguists. This research attempts to shed light on an aspect of Dr. Tamam Hassan's efforts in the field of linguistic sound, who is one of the linguists in the modern era, presenting these linguistic efforts and vocal opinions on the slcale of linguistic criticism and comparing it with the rulings of the first Arab scholars, and showing the originality of the Arabic phonemic lesson and its superiority in many aspects to what was presented by the modernizers, by comparing Dr.Tamam Hassan’s vocal views and rulings with the first Arab scales in the field of linguistic sound.I hope that this research provided examples of this vision of the audio research by Dr. Tamam Hassan and many modern scholars.
Keywords: Reflections on the research of Dr. Tammam Hassan